A Prototype Executive Information System For The Ski Industry - Dossa, Karim; Williams, Peter (Téoros, 1995)
In few other areas of activity are the generation, gathering, processing, application and communication of information as important for business as they are in the travel and tourism industry. Ski area executives need to understand their markets in order to effectively interact with them. For this, managers have to be able to generate enough timely information about the market to support their decision making processes. This study develops a prototype ski executive information system for the Canadian ski industry. It is designed to provide ski industry executives with a readily accessible source of product and marketing intelligence to assist in strategic decision making. The icon and menu based grapical interfaces developed in this prototype combine to provide a user friendly information retrieval system whose efficiencies could eventually provide a botter use of various tourism data bases by decision makers.